Data-Driven Insights: A Decade of Sol Plaatje University's Research Journey and Development - Mosia, Moeketsi (Research in Social Sciences and Technology- OpenED Network, 2024)
This paper analyses Sol Plaatje University's (SPU) progress on increased research activities. The paper employs bibliometric analysis review method to demonstrate the university's transition from being a predominantly teaching-focused to a more research-oriented institution. A novel, data-driven methodology is also adopted in this paper, to identify and examine SPU’s research niche through publications. This paper’s data were collected from the Scopus and Web of Science databases. The paper’s findings reveal that there was an overall significant increase in research outputs, observable on yearly basis for a decade (2014 to 2023). The yearly increase in research output is recorded from diverse research fields, including machine learning, cryptography, environmental research, and public health. Findings further reveal that SPU has built its international research collaborations within the African and European continents. This paper’s findings contribute to literature on higher education development by offering insights into how newly established universities can transition from a teaching-centric focus to becoming research-active. This paper revealed the importance of strategic planning, interdisciplinary research, and international collaboration in the development of a vibrant research environment.